Intestinal parasites of Leopardus geoffroyi (Mammalia, Felidae) inhabiting the Paraná River Delta (Argentina): a coprological study - Zonta, María Lorena (2019)
Leopardus geoffroyi (Geoffroy’s cat) is distributed from southern Brazil and Bolivia to southern Argentina and Chile in the Patagonia region. The aim was to identify intestinal parasites of L. geoffroyi inhabiting the Paraná River Delta (Buenos Aires province, Argentina) and to detect species of zoonotic importance. Thirteen fecal samples were obtained from specimens captured. Feces were processed using Ritchie and Sheather modified techniques. Prevalence and dominance were calculated for each parasite species found. All samples were parasitized. Twelve parasite species were identified. Polyparasitism was observed in all cats. Aelurostrongylus abstrusus, Spirometra sp., Ancylostoma sp. and Toxocara cati were the most prevalent and dominant species. Eimeria sp., Rodentolepis nana, Platynosomum sp., Eucoleus aerophilus, Pterygodermatites sp., Spirurida, Trichuris sp. and Trichostrongyloidea were also detected. This study reports A. abstrusus, Spirometra sp., R. nana and Platynosomum sp. for the first time in the Geoffroy’s cat for Argentina. Species of zoonotic importance such as Spirometra sp., Ancylostoma sp., T. cati, E. aerophilus, Trichuris sp. and R. nana are recorded. The diversity of endoparasites found in the Geoffroy’s cat responds to the generalist habits of this carnivore and to its interaction with domestic animals, which favors the transmission of parasites of zoonotic importance.